Beneficial and potentially harmful compounds in edible mushrooms cultivated on substrates supplemented with algal wracks from Mar Menor lagoon seashore - Sara Figueredo; Rebeca Lavega; Luis Vázquez; Carlos García-Delgado; Francisco R. Marin; Alejandro Ruiz-Rodriguez; Cristina Soler-Rivas (Biocatalysis and Agricultural Biotechnology, 2026)

Screening of enzyme-producing mushroom species able to grow on beach wracks from Mar Menor lagoon for their valorization - Sara Figueredo; Alejandro Ruiz-Rodriguez; Francisco R. Marín; Cristina Soler-Rivas (Journal of Applied Phycology, 2026)
Large amounts of algal beach wracks are accumulating on the shores of the Mar Menor lagoon due to its ecological imbalance. This biomass is collected and discarded in landfills without any added value. In an attempt to valorize this material, semi-solid media including dried algal wracks with or without prior dialysis, wheat straw and mycological malt extract agar (as control) were prepared to cultivate edible mushroom mycelia. The fungal enzymatic activities were analyzed to assess their potential to produce valuable enzymes for biotechnological applications, such as the food industry. The results indicated that Agaricus bisporus , Pleurotus ostreatus , Pleurotus ferulae , Flammulina velutipes , Hypsizygus tessulatus , Pholiota nameko , and Lentinula edodes could grow on both dialyzed and non-dialyzed algal wracks, while Ganoderma lucidum showed poor growth. Notably, most species produced more biomass on the algal wracks than on wheat straw, a standard substrate for mushroom cultivation. Non-dialyzed algal wracks stimulated the production (intramycelial) and secretion (extramycelial) of xylanases, particularly in L. edodes , F. velutipes , and H. tessulatus . When grown on dialyzed wracks, cellulase activity was mainly enhanced in P. ferulae , F. velutipes , and A. bisporus , and proteolytic activity was highest in F. velutipes and H. tessulatus . In contrast, the wracks were not suitable for inducing α-amylase activity. The production of laccases and peroxidases was more species-dependent than influenced by the tested substrate.

Utilization of algal beach wracks as a supplementary substrate for enhancing mushroom production - Rebeca Lavega; Emilio Rascón; Cristina Soler-Rivas; Margarita Pérez-Clavijo (Frontiers in Marine Science, 2025)
Despite ecological protections, the Mar Menor lagoon in Spain continues to experience eutrophication, leading to uncontrolled proliferation of algae such as Caulerpa prolifera . When it decomposes, it reduces oxygen and creates sludge, causing fish and other aquatic animals to suffocate. Storms and seasonal changes then wash the uprooted algae ashore, generating foul odors and sludge buildup along the lagoon’s banks. In this study, the utilization of algal beach wracks as a component of substrates for mushroom cultivation was explored, assessing their potential to replace conventional lignocellulosic materials. Rinsed algal wracks were incorporated at 20%, 40%, and 60% (dry weight) into wheat straw-based substrates (patented formula no. 202430026), supplemented with 0%, 0.63%, 2.5%, or 5% additional nutrients, to cultivate four different mushroom species: oyster mushrooms ( Pleurotus ostreatus ), king oyster mushrooms ( Pleurotus eryngii ), Shimeji mushroom ( Hypsizygus tessulatus ), and Nameko mushroom ( Pholiota nameko ). Proximal analysis [moisture, pH, conductivity, nitrogen, organic load, and carbon/nitrogen (C/N) ratio], lignocellulosic content (lignin, cellulose, and hemicellulose), mushroom yield, and biological efficiency (BE) were analyzed and compared among formulations. Results demonstrated that utilizing 20% algal wracks significantly enhanced BE, with increases above 300% for H. tessulatus , 11% for P. ostreatus , and 9% for P. nameko , while P. eryngii showed similar yield and BE to the standard substrate (46.53% BE in the standard substrate compared to 48.37% in the algae-enriched substrate). These findings highlight the feasibility and environmental value of using algal beach residues as sustainable substrates for mushroom production, offering a circular bioeconomy alternative to current disposal practices in the Mar Menor region.

Reducing cellular inflammation and oxidation by supercritical CO2 extracts from edible-medicinal mushrooms - María de las Nieves Siles-Sánchez; Paula García-Ponsoda; Eva Tejedor-Calvo; Susana Santoyo; Alejandro Ruiz-Rodríguez; Rebeca Lavega; Laura Jaime; Cristina Soler-Rivas (Food Research International, 2025)

Extraction and trapping of truffle flavoring compounds into food matrices using supercritical CO2 - Eva Tejedor-Calvo; Pedro Marco; Peter Spègel; Cristina Soler-Rivas (Food Research International, 2023)

Effect of tartrazine on digestive enzymatic activities: in vivo and in vitro studies - Fatma Zohra Ameur; Nabila Mehedi; Cristina Soler Rivas; Antonio Gonzalez; Omar Kheroua; Djamel Saidi (Toxicological Research, 2020)

Effect of domestic processing on bioactive compounds - Alejandro Ruiz-Rodriguez; Francisco R. Marín; Aurelio Ocaña; Cristina Soler-Rivas (Phytochemistry Reviews, 2008)